1729. Effect of Glove Disinfection on Bacterial Contamination of Healthcare Worker Hands. (26th November 2018) - Robinson, Gwen; Kpadeh, Zegbeh Z; Alserehi, Haleema; Morgan, Daniel; Harris, Anthony D; Johnson, J Kristie; Leekha, Surbhi
Abstract: Background: Disinfection of gloves and gowns was recommended to decrease healthcare worker (HCW) self-contamination during doffing of gloves and gowns in the Ebola epidemic. To understand the potential role of this practice in preventing bacterial transmission, we examined the effect of disinfectants on bacterial contamination of HCW hands following glove removal. Methods: A laboratory simulation study was conducted using methicillin-susceptible Staphylococcus aureus and antibiotic-sensitive Klebsiella pneumoniae among volunteer HCWs ( n = 10 per organism). For each experiment, the volunteer donned 2 pairs of gloves with the "under glove" simulating HCW hands and "top glove" simulating actual glove use in the clinical setting. The top-glove was inoculated with 10 8 CFU bacteria for each step. Top gloves were sampled directly after inoculation (Arm A), and after disinfection with alcohol gel, bleach wipes, and quaternary ammonium (quat) wipes, in separate steps (Arm B). Under gloves were sampled after top glove removal without disinfection (Arm C), and top glove removal post disinfection (Arm D). Quantitative bacterial load reduction was compared for glove use (Arm C − Arm A), and for disinfectant use in addition to glove use (Arm D − Arm C). Qualitative detection of any bacterial load (present/absent) on under glove in the setting of disinfection prior to top glove removal was also assessed. Results: Of 10 8 CFU inoculated, the median recovery was 1.2 × 10 4 CFU (both bacteria combined). After glove removal (no disinfection), the median recovery from the under glove was 2.7 × 10 2 CFU, for a reduction of 98% (1.6 log) in bacterial load. After top glove disinfection and removal, the median bacterial recovery from the under glove was 1.4 × 10 2, 0, and 0 CFU for alcohol, quat, and bleach (47% or 0.3 log reduction for alcohol; 99% or 2 log reduction for quat and bleach) (Figure 1). Regardless of quantity, bacteria were recovered from under gloves even after top glove disinfection in 70%, 40%, and 35% cases for alcohol, quat, and bleach, respectively (Figure 2). Conclusion: Glove disinfection prior to glove removal is effective at reducing bacterial contamination of HCW hands. However, despite disinfection, some level of hand contamination occurs frequently. Disclosures: J. K. Johnson, Q-Linea: Investigator, Research grant. Applied Biocode: Investigator, Research grant